Dynamic Imaging of Nanostructures in an Electrolyte with a Scanning Electron Microscope. (February 2021) - Yoon, Aram; Herzog, Antonia; Grosse, Philipp; Alsem, Daan Hein; Chee, See Wee; Roldán Cuenya, Beatriz
Abstract: Abstract: The development of microfabricated liquid cells has enabled dynamic studies of nanostructures within a liquid environment with electron microscopy. While such setups are most commonly found in transmission electron microscope (TEM) holders, their implementation in a scanning electron microscope (SEM) offers intriguing potential for multi-modal studies where the large chamber volume allows for the integration of multiple detectors. Here, we describe an electrochemical liquid cell SEM platform that employs the same cells enclosed by silicon nitride membrane windows found in liquid cell TEM holders and demonstrate the imaging of copper oxide nanoparticles in solution using both backscattered and transmitted electrons. In particular, the transmitted electron images collected at high scattering angles show contrast inversion at liquid layer thicknesses of several hundred nanometers, which can be used to determine the presence of liquid in the cell, while maintaining enough resolution to image nanoparticles that are tens of nanometers in size. Using Monte Carlo simulations, we show that both imaging modes have their advantages for liquid phase imaging and rationalize the contrast inversion observed in the transmitted electron image.